Effectiveness Of Use Of Interactive E-Poster History Learning Media In Increasing History Awareness - Sumantri, Pulung; Nababan, Surya Aymanda; Sumanti, Solihah Titin; Tanjung, Yushar; Mulyani, Fini Fajri; Md. Jali, Jafalizan (Jurnal Ilmu Pendidikan, 2024)
Historical awareness is one of the historical thinking skills that students must have. Historical awareness is related to the identity of a nation related to the past. This research aims to determine the effectiveness of interactive E-Poster media in increasing students' historical awareness. This research uses the Pretest-Posttest Control Group experimental method, consisting of an experimental and control group. The sample consisted of 50 class XII high school students selected using a random sampling technique. The data instruments used are the results of pretests and posttests carried out by students. This research indicates a significant difference in students' historical awareness before and after using the E-Poster learning media. The T-test results show a significance value of 0.000, less than 0.005, with the conclusion that the use of interactive e-posters has an influence on students' historical awareness. This increase can be seen in the N-Gain test results, which show a score of 0.75 or 75 percent, assuming an increase in students' historical awareness using e-poster media by 75 percent. This research concludes that using e-poster learning media is effective in history learning, especially in increasing students' historical awareness